Calculation of Rack Medical Record Storage in the Filling Room of Anna Medika General Hospital Madura - Rulisiana Widodo (JURNAL MEDICAL P-ISSN : 2685-7960 e-ISSN : 2685-7979, 1970)
Filing is an activity that stores, manages, maintains and collects medical records. Medical records stored in filing include outpatient medical records, inpatient care, and emergency medical records.Therefore, the medical record must always be well-protected from the risk of loss and damage due to insects, temperature, etc. The condition of the availability of medical record storage shelf at Anna Medika General Hospital Madura is used as one place for outpatient medical record, inpatient care and emergency care. where this is considered ineffective because the shelf design is not in accordance with the standard.The purpose of this study was to determine the condition of the medical record file storage room and calculate storage rack requirements for the next five years using the IFHRO method. Data collection through interviews and observation.